Tendencies Affecting the Growth and Cultivation of Genus Spirulina: An Investigative Review on Current Trends - Nawal K. Z. AlFadhly; Nawfal Alhelfi; Ammar B. Altemimi; Deepak Kumar Verma; Francesco Cacciola (Plants, 2022)
Spirulina, a kind of blue-green algae, is one of the Earth’s oldest known forms of life. Spirulina grows best in very alkaline environments, although it may flourish across a wide variety of pH values. There are several techniques for growing Spirulina spp., ranging from open systems such as ponds and lakes, which are vulnerable to contamination by animals and extraterrestrial species, to closed systems such as photovoltaic reactors, which are not. Most contaminated toxins come from other toxic algae species that become mixed up during harvest, necessitating the study of spirulina production processes at home. Lighting, temperature, inoculation volume, stirring speed, dissolved particles, pH, water quality, and overall micronutrient richness are only a few of the environmental parameters influencing spirulina production. This review article covers the conditions required for spirulina cultivation, as well as a number of crucial factors that influence its growth and development while it is being grown. In addition, the article discusses harvesting processes, biomass measurement methods, the identification of dangerous algae, and the risk of contaminating algae as it grows on cultures. Spirulina’s rising prospects as food for human consumption are a direct outcome of its prospective health and therapeutic advantages.